2013
DOI: 10.1007/s00125-013-2965-2
|View full text |Cite
|
Sign up to set email alerts
|

Roux-en-Y gastric bypass vs sleeve gastrectomy for obese patients with type 2 diabetes: a randomised trial

Abstract: This work was supported by grant no. 3-000-8480 from the Israel Ministry of Health Chief Scientist, the Stephen Morse Diabetes Research Foundation and by Johnson & Johnson.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
93
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 117 publications
(101 citation statements)
references
References 10 publications
4
93
1
3
Order By: Relevance
“…Thus, it may be argued that the true early effects of LSG on metabolic control are even greater compared to baseline levels since it needs to overcome operation-related stress. In addition to the immediate postoperative glycemic response, results of the current study's subsequent follow-up also concur with previous research of LSG, which focused on longer postoperative periods (3 months onwards) [19,26]. In addition to the glycemic effects detected in the immediate postoperative period in the current study, extended follow-up also detected changes in fasting glucose and C-peptide, representing wider glycemic effects of surgery.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, it may be argued that the true early effects of LSG on metabolic control are even greater compared to baseline levels since it needs to overcome operation-related stress. In addition to the immediate postoperative glycemic response, results of the current study's subsequent follow-up also concur with previous research of LSG, which focused on longer postoperative periods (3 months onwards) [19,26]. In addition to the glycemic effects detected in the immediate postoperative period in the current study, extended follow-up also detected changes in fasting glucose and C-peptide, representing wider glycemic effects of surgery.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies [7,19] have discussed earlier metabolic changes subsequent to bariatric surgery, demonstrating improvement in diabetic parameters (such as fasting plasma glucose and hemoglobin A1C) as early as 3 months after surgery, related to weight loss. Limited evidence exists regarding the effect of surgery on diabetes mellitus in earlier postoperative periods.…”
Section: Introductionmentioning
confidence: 98%
“…However, there is no consensus on this topic in the literature. There are studies advocating that both techniques have no significant superiority over each other in terms of blood glucose and HbA1c levels (14). According to the results of our study, LRYGB was not found to have a statistically significant superiority over LSG in terms of diabetes remission rate.…”
Section: Discussioncontrasting
confidence: 67%
“…A. Keidar и соавт. [28] приводят данные о том, что через 3 мес после операции не выявляется значимой разницы между концентрацией гликированного гемоглоби-на (6,23±0,69% и 6,37±0,71%) у пациентов, исход-но страдавших сахарным диабетом и перенесших ЛРРЖ (18 случаев) и ЛЖШ (19 случаев). С другой стороны, J. Li и соавт.…”
Section: Discussionunclassified